Visual and radiographic merged-ICDAS caries progression pattern in 2-6 years old Colombian children: two-year follow-up (2019)
Aim: To describe the 2-year clinical and combined with radiographic caries progression pattern in three cohorts of 2-(a), 4-(b), and 6-yr-old children (c). Design: Baseline sample comprised 600 children (each-cohort: n = 200). Children's dental surfaces were clinically assessed at schools without air-drying (epi) in terms of: Clinical (C) caries lesions (d/D) with ICDASepi-merged system (C-ICDASepi-d/D:Sound/Initial-epi/Moderate/Extensive); fillings (f/F), and missing teeth (m/M). Clinical ICDAS (C) and Radiographic ICDAS (R) indexes were combined (C + R). Caries experience (dmf + DMF) was expressed as: C-dmfs + DMFS (Moderate/Extensive-d/D); C-ICDASepi-dmfs + DMFS (including Initial-epi-d/D); C + R-dmfs + DMFS; and C + R-ICDASepi-dmfs + DMFS. Follow-up caries progression corresponded to more severe caries score. Results: Two-year follow-up sample was n = 352 (58.7%-baseline sample): a: n = 81; b: n = 131; c: n = 140. Around 100% of children presented C + R-ICDASepi-dmf + DMF ≥ 1, with following C + R-ICDASepi-dmfs + DMFS means: a: 7.3 ± 14.1; b: 12.2 ± 19.5; c: 13.3 ± 16.9. Progression was about 60% in all cohorts, mainly corresponding, in cohort b and c, to occlusal and distal surfaces of lower first/second-molar-primary teeth, and in cohort a to buccal surfaces of upper primary-incisor teeth. The addition of radiographs increased caries mean and prevalence in 10% as compared to only visual examination. Conclusions: Children showed a high C + R caries experience progression rate, mainly related to occlusal and proximal surfaces in lower-molar teeth and buccal in upper-incisor teeth.